Past and Present Scenario of Imaging Infection and Inflammation: A Nuclear Medicine Perspective - Dipti Kakkar; Anjani K. Tiwari; Harpal Singh; Anil K. Mishra (Molecular Imaging, 2012)
Nuclear medicine techniques provide potential non-invasive tools for imaging infections and inflammations in the body in a precise way. These techniques are further exploited by the use of radiopharmaceuticals in conjunction with imaging tests such as scintigraphy and positron emission tomography. Improved agents for targeting infection exploit the specific accumulation of radiolabeled compounds to understand the pathophysiologic changes involved in the inflammatory process and correlate them with other chronic illnesses. In the recent past, a wide variety of radiopharmaceuticals have been developed, broadly classified as specific radiopharmaceuticals and nonspecific radiopharmaceuticals. New developments in positron emission (leveraging 18 F and 18 fluorodeoxyglucose) and heterocyclic/peptide chemistry and radiochemistry are resulting in unique agents with high specific activity. Various approaches to visualizing infection and inflammation are presented in this review, in an integral manner, that give a clear view of the existing radiopharmaceuticals in clinical practice and those under development.